2019
DOI: 10.1016/j.joca.2018.08.024
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the small molecule studies of osteoarthritis using nuclear magnetic resonance and mass spectroscopy

Abstract: s u m m a r yObjective: To perform a systematic review of the small molecule metabolism studies of osteoarthritis utilising nuclear magnetic resonance (NMR) or mass spectroscopy (MS) analysis (viz., metabolomics or metabonomics), thereby providing coherent conclusions and reference material for future study. Method: We applied PRISMA guidelines (PROSPERO 95068) with the following MESH terms: 1. "osteoarthritis" AND ("metabolic" OR "metabonomic" OR "metabolomic" OR "metabolism") 2. ("synovial fluid" OR "cartila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…Both OA and RA are characterized by altered lipid metabolism, and lipids have been proposed to play several roles in their pathogeneses [ 7 9 ]. Increased body fat mass is a risk factor for OA development, as it induces mechanical stress, especially in the tibiofemoral joint, and causes systemic low-grade inflammation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both OA and RA are characterized by altered lipid metabolism, and lipids have been proposed to play several roles in their pathogeneses [ 7 9 ]. Increased body fat mass is a risk factor for OA development, as it induces mechanical stress, especially in the tibiofemoral joint, and causes systemic low-grade inflammation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the lipid peaks in 25BCS provided stronger NMR peaks from the (CH 2 ) n moiety (41). Higher levels of choline and 3hydroxyisobutyrate in the 25BCS samples suggest a destruction of complex lipid species and fatty acid metabolism (50). Alternatively, it could indicate a high level of gluconeogenesis.…”
Section: Metabolic Differences Between 25bcs and Hsfmentioning
confidence: 95%
“…The presence of active joint in ammation reduces the oxygen tension and yields an anaerobic state (48,49). Animal studies of osteoarthritic synovial uid compared to healthy controls found an elevation in anaerobic metabolism, fatty acid chain oxidation and proteoglycan degradation (50). The free oxygen of bovine and human arterial blood is similar(51, 52).…”
Section: Metabolic Differences Between 25bcs and Hsfmentioning
confidence: 99%
See 1 more Smart Citation
“…As metabolites can be used as biomarkers, circulating metabolites or those in urine may be indicative of underlying pathologies. There are a vast number of metabolite changes that have been identified in both blood and synovial fluid of OA patients [13], suggesting that metabolites could influence the various OA pathological features or associated comorbidities in both the local disease environment and in distant organs.…”
Section: Introductionmentioning
confidence: 99%